Lieutenant Bones - Wallace, Edgar (Saga Egmont, 2023)
It is a time when the major world powers are vying for colonial honors, a time of juju, witch doctors, and an uneasy peace with Bosambo, the impressive chief of the Ochori. When Commissioner Sanders goes on leave, the trusty Lieutenant Hamilton takes over administration of the African territories. However, yet again, the trouble-prone Bones, while meaning to assist, only manages to spread his own unique style of innocent and endearing mischief.